2020
DOI: 10.1080/14760584.2020.1873770
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact analysis of introducing a non-reconstituted, hexavalent vaccine for pediatric immunization in the United Kingdom

Abstract: Objectives: Non-reconstituted, hexavalent vaccines (HV-NRs) can facilitate clinical practice by shortening vaccine preparation and administration time and by reducing the risk of vaccination errors compared to combination vaccines requiring reconstitution. The aim of this study was to determine the budget impact of introducing an HV-NR into the United Kingdom's (UK) pediatric immunization program, which currently uses a hexavalent vaccine requiring reconstitution (HV-R). Methods: Abudget impact model covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…An earlier study estimated the budget impact of introducing a fully liquid or readyto-use hexavalent vaccine into the United Kingdom's pediatric immunization program compared with another hexavalent vaccine requiring reconstitution. The study supported the advantages of fully liquid vaccines over reconstituted vaccines having the potential of cost savings by shortening vaccine preparation time and reducing the risk of vaccination error [19]. Similar results were seen when introducing the ready-to-use hexavalent vaccine into the national vaccination program in Peru that reduce total costs due to lower time costs despite an increase in vaccine costs [21].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…An earlier study estimated the budget impact of introducing a fully liquid or readyto-use hexavalent vaccine into the United Kingdom's pediatric immunization program compared with another hexavalent vaccine requiring reconstitution. The study supported the advantages of fully liquid vaccines over reconstituted vaccines having the potential of cost savings by shortening vaccine preparation time and reducing the risk of vaccination error [19]. Similar results were seen when introducing the ready-to-use hexavalent vaccine into the national vaccination program in Peru that reduce total costs due to lower time costs despite an increase in vaccine costs [21].…”
Section: Discussionsupporting
confidence: 73%
“…These findings were the incentives to investigate more in depth the rates of infection of pentavalent vaccines to be reconstituted versus the hexavalent vaccine that is ready to be used and estimate their cost difference. Studies on the economic value of the hexavalent vaccine suggested the following costs to be assessed: cost of the vaccine, cost of inpatient and/or outpatient visits, delivery cost, time cost, labor cost, cost for immunization errors and adverse events, and waste cost [ 18 , 19 , 20 , 21 ]. Our study adds the cost of infection contamination following immunization using the results of a model construct.…”
Section: Introductionmentioning
confidence: 99%
“…The fully liquid formulation of MenACYW-TT [55] and its good stability (shelf life: 42 months) are distinctive features that offers the advantage of convenience and the benefit of being able to eliminate reconstitution errors [98][99][100]. The advantages of liquid formulation vaccines compared to those needing reconstitution have been shown for different vaccines, in terms of saving time, preventing administration errors, and helping to keep costs down [101][102][103][104].…”
Section: Expert Opinionmentioning
confidence: 99%
“… 9 Use of hexavalent vaccine can also reduce the total cost of vaccination. 10 For example, a study by Mathijssen and colleagues 11 showed that the integration of hexavalent vaccine into the national immunization program of the United Kingdom could reduce vaccination costs by 9.07 million pounds over 10 years, and other studies have shown that hexavalent vaccine can save both direct and indirect healthcare costs for workers and parents. 6 , 10 Once a combination vaccine is approved as a safe and effective vaccine, there can be barriers to its use.…”
Section: Introductionmentioning
confidence: 99%